Forge your future - Kalam, APJ Abdul (Delhi Rajpal, 2022)
(3z(BForge your Future(3y (Bis a well written novel by A.P.J. Abdul Kalam. Dr. Kalam had to overcome various obstacles since humble childhood to becoming the president of India. s
Keywords: President